A Comparison of the Effects of Cognitive-Behavioral Couple Therapy and Emotionally-Focused Couple Therapy on Love Schemas of Married Women - Shahmoradi, Mahnaz; Nicknam , Mojgan; Khakpour, Reza (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to compare the effects of cognitive-behavioral couple therapy and emotionally-focused couple therapy on the love schemes of married women. Methods: The present quasi-experimental study had a pretest-posttest design with a control group and a two-month follow-up. The statistical population consisted of married 25-40-year-old women who visited counseling centers in Tehran in 2018. Among them, 60 married women were selected after screening with the love schema questionnaire by Singelis et al. (1995) using the convenience sampling method and were randomly divided into two groups, experimental and control (20 women per group). The experimental group received the cognitive-behavioral couple therapy by Shadish and Baldwin (2005) in 10 sessions, and the emotionally-focused couple therapy by Johnson (2004) in eight sessions for 90 minutes. The. Results: The cognitive-behavioral couple therapy intervention affected secure love schema (P=0.019, F=5.98), clingy love schema (P=0.004, F=9.20), skittish love schema (P=0.006, F=8.55), fickle love schema (P=0.007, F=8.15), casual love schema (P=0.022, F=5.71), and disinterested love schema (P=0.003, F=9.99). The emotionally-focused couple therapy intervention also affected secure love schema (P=0.004, F=9.18), Clingy love schema (P=0.007, F=8.23), Skittish love schema (P=0.028, F=5.21), Fickle love schema (P=0.001, F=12.81), Casual love schema (P=0.019, F=6.01), and disinterested love schema (P=0.002, F=10.65), and the effect was stable in the follow-up phase. Conclusion: Cognitive-behavioral couple therapy and emotionally-focused couple therapy are effective interventions in improving women's love schema; hence, the findings provide important implications for the education and promotion of mental health in married women.